PENGARUH BEBAN KERJA, LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA BENDAHARA PENGELUARAN PADA SATKER JAJARAN POLDA MALUKU - Gresye Leatemia; Ferdy Leuhery; Felix Chandra (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to analyze the effect of workload, work environment and job satisfaction on the performance of spending treasurers in the work units of the Maluku Regional Police. The background of this research is the Performance of Expenditure Treasurers at the Moluccas Polda Satker where there are several personnel who are dissatisfied with the results of their work because the results of the work carried out by Financial staff at the Maluku Polda Satker are often not assessed well by partners and leaders where the results of the work carried out have not received maximum value in managing and financial accountability. This study uses quantitative research by collecting data that is measured using statistical, mathematical and computational techniques. With a total sample of 80 (eighty) respondents. And using regression analysis with the help of SPSS 21 software. The findings from this study indicate that workload has a positive and insignificant impact on the Performance of Treasurers for Spending SATKER Staff of the Maluku Regional Police, the Work Environment has a positive and insignificant impact on the Performance of Treasurers of Spending SATKER for the Maluku Regional Police. As for Job Satisfaction, it has a positive and insignificant impact on the Performance of the Treasurer's Expenditures for Work Units for the Maluku Regional Police.